Security threats of finger print biometric in network system environment - Taha, Imad; Ahmad, Mohammad A. (Design for Scientific Renaissance, 2011)
Biometrics-based personal authentication systems that use physiological (e.g., fingerprint, face) or behavioral (e.g., speech, handwriting) traits are becoming increasingly popular, compared to traditional systems that are based on tokens (e.g., key) or knowledge (e.g., password). On the other hand, biometric systems are vulnerable to attacks, which can decrease their security. This paper analyzes and surveys the vulnerabilities and security threats of the finger print biometric systems used for access control and the authentication of access to confidential information in network system environment. As analysis tools, two biometric network models are implemented and connected to see some of the arguments of the vulnerabilities and security threats. Based on that, analysis and surveying, experimental solutions and countermeasures are presented.